2018
DOI: 10.1093/mnras/sty1783
|View full text |Cite
|
Sign up to set email alerts
|

An asteroseismic view of the radius valley: stripped cores, not born rocky

Abstract: Various theoretical models treating the effect of stellar irradiation on planetary envelopes predict the presence of a radius valley: i.e. a bimodal distribution of planet radii, with super-Earths and sub-Neptune planets separated by a valley at around ≈ 2 R ⊕ . Such a valley was observed recently, owing to an improvement in the precision of stellar, and therefore planetary radii. Here we investigate the presence, location and shape of such a valley using a small sample with highly accurate stellar parameters … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

49
445
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 458 publications
(497 citation statements)
references
References 33 publications
49
445
3
Order By: Relevance
“…The host star plays an important role in the evolution of its protoplanetary disc for multiple reasons, including determining planetary compositions, affecting the location where grains can condense from the disk, the clearing of the disc via stellar winds (Ercolano & Pascucci 2017), and the timescale for the end of planetesimal accretion. The planet radius valley (Fulton et al 2017;Van Eylen et al 2018;Hsu et al 2019) for planets around FGK-dwarfs is often cited as evidence for the influence of stellar irradiance on planet formation. While photoevaporation (e.g.…”
Section: Comparison To Fgk Occurrence Ratesmentioning
confidence: 99%
“…The host star plays an important role in the evolution of its protoplanetary disc for multiple reasons, including determining planetary compositions, affecting the location where grains can condense from the disk, the clearing of the disc via stellar winds (Ercolano & Pascucci 2017), and the timescale for the end of planetesimal accretion. The planet radius valley (Fulton et al 2017;Van Eylen et al 2018;Hsu et al 2019) for planets around FGK-dwarfs is often cited as evidence for the influence of stellar irradiance on planet formation. While photoevaporation (e.g.…”
Section: Comparison To Fgk Occurrence Ratesmentioning
confidence: 99%
“…They argued that the underlying astrophysical effect could be photoevaporation, whereby stellar incident flux strips a planet's H/He atmosphere if the atmosphere is not thick enough, leaving a population of stripped, rocky planets and an untouched population of larger, gaseous mini-Neptunes (Owen & Wu 2013;Lopez & Rice 2016;Owen & Wu 2017;Van Eylen et al 2017). As an alternative hypothesis, they also suggested that gas accretion could be delayed during planet formation until the protoplanetary disk is already gas poor, creating a population of small, rocky planets (Lee et al 2014;Lee & Chiang 2016).…”
Section: The Planet Radius Distributionmentioning
confidence: 99%
“…At R < 4 R ⊕ , most confirmed exoplanets are sub-Neptunes: worlds with R = 1.6 − 3.2 R ⊕ and density < 4 g/cc (e.g., Rogers 2015;Wolfgang et al 2016). Sub-Neptunes probably have 10 3 -10 4 -km-deep H 2 -rich atmospheres cloaking rocky cores (e.g., Owen & Wu 2017;Van Eylen et al 2018), at least for orbital period < 100 d. This implies that sub-Neptunes are mostly atmosphere by volume, and mostly silicate by mass ( Fig. 1).…”
Section: Introductionmentioning
confidence: 96%